Incidence, Risk Factors, and Outcomes of Transition of Acute Kidney Injury to Chronic Kidney Disease in Cirrhosis: A Prospective Cohort Study. Issue 3 (24th October 2019) - Maiwall, Rakhi; Pasupuleti, Samba Siva Rao; Bihari, Chhagan; Rastogi, Archana; Singh, Pawan Kumar; Naik, Vini; Singh, Akanksha; Jain, Priyanka; Kumar, Awinash; Mukund, Amar; Mathur, R.P.; Kumar, Guresh; et al.
Abstract : Transition to chronic kidney disease (CKD) after an episode of acute kidney injury (AKI) is known in patients without cirrhosis. We studied the incidence and risk factors for development of CKD in patients with cirrhosis. Competing risk analysis was performed to identify risk factors for CKD development. Of 818 patients with cirrhosis (age, 50.4 ± 11.8 years; 84% males; Model for End‐Stage Liver Disease [MELD], 19.9 ± 9.9), 36% had AKI at enrollment, 27% had previous AKI, and 61% developed new episodes of AKI during the follow‐up period. CKD developed in 269 (33%) patients. Serum cystatin C (CysC; subdistribution hazard ratio [SHR], 1.58; 1.07‐2.33), episodes of previous AKI (SHR, 1.26; 1.02‐1.56), and AKI stage at enrollment (no AKI [SHR, 1] vs. stage 1 [SHR, 3.28; 1.30‐8.25] vs. stage 2 [SHR, 4.33; 1.76‐10.66] vs. stage 3 [SHR, 4.5; 1.59‐12.73]) were identified as baseline risk factors for CKD development. On time‐varying competing risk analysis, MELD (SHR, 1.01; 1.00‐1.03), number of AKI episodes (SHR, 1.25; 1.15‐1.37), and CysC (SHR, 1.38; 1.01‐1.89) predicted CKD development. Development of CKD was associated with higher risk of death. Reduction in glomerular filtration rate (GFR) not meeting CKD criteria was observed in 66% of patients with cirrhosis, more so in those with previous AKI episodes and a high CysC level and MELD score. Renal histology, available in 55 patients, showed tubulointerstitial injury in 86%, cholemic nephrosis in 29%, and glomerular changes in 38%. Conclusion: Almost two‐thirds of patients with cirrhosis develop episodes of AKI and reduction in GFR; one‐third progress to CKD, resulting in adverse outcomes. Higher MELD and CysC levels and number of AKI episodes predict development of CKD in patients with cirrhosis.